Statul bunăstării sociale și calitatea vieții - Frigioiu, Nicolae (Calitatea Vieții, 1990)
A distinction is made between the welfare economy and the sociai welfare state: the former is ruled by positive economics, and the latter by normative economics, implying ethics of income redistribution and paternalistic ethos. Social policies based on normative economics have been mainly developed by the social welfare state of social-democratic inspiration. They led to a higher QL due to: humanized work conditions, democratization of work relations, security of labour force occupation, a higher quality of the natural and cultural environment etc.